Cutaneous melanoma in women - Mi Ryung Roh, MD; Philip Eliades, BS; Sameer Gupta, BA; Jane M. Grant-Kels, MD; Hensin Tsao, MD, PhD (Wolters Kluwer, 2017)
Background: Gender disparity in melanoma outcome is consistently observed, suggesting that gender is as an important prognostic factor. However, the source of this gender disparity in melanoma remains unclear. Objective: This article reviews advances in our understanding of gender differences in melanoma and how such differences may contribute to outcomes. Methods: A broad literature search was conducted using the PubMed database, with search terms such as 'gender differences in melanoma' and 'sex differences in melanoma.' Additional articles were identified from cited references. Results: Herein, we address the gender-linked physiologic differences in skin and melanoma. We discuss the influence of estrogen on a woman's risk for melanoma and melanoma outcomes with regard to pregnancy, oral contraceptives, hormone replacement therapy, and UV tanning. Conclusions: The published findings on gender disparities in melanoma have yielded many advances in our understanding of this disease. Biological, environmental, and behavioral factors may explain the observed gender difference in melanoma incidence and outcome. Further research will enable us to learn more about melanoma pathogenesis, with the goal of offering better treatments and preventative advice to our patients.